1979
DOI: 10.1111/j.1432-1033.1979.tb06277.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Tryptophan Synthase from Saccharomyces cerevisiae and Partial Activity of Its Nicked Subunits

Abstract: Enzymes can be reconstituted with high yield after dissociation and deactivation in strong denaturants. This finding can be utilized to separate proteases and other impurities (with molecular weights differing under denaturing conditions from the subunit molecular weight of the enzyme to be purified) from the desired enzyme. Applying this approach to tryptophan synthase from yeast, a homogeneous preparation with a molecular weight of 154000 Jr 5000 and a specific activity of 1200 & 100 Yanofsky units/mg has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…When this manuscript was completed we were informed that Bartholmes et al [48] had arrived at essentially the same conclusions as reported in this paper, using a different method for purifying tryptophan synthase from S. cerevisiae.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…When this manuscript was completed we were informed that Bartholmes et al [48] had arrived at essentially the same conclusions as reported in this paper, using a different method for purifying tryptophan synthase from S. cerevisiae.…”
Section: Discussionmentioning
confidence: 68%
“…The maximum specific activity is estimated to be approximately 1200 units/mg protein, which is half as large as estimated for the maximum specific activity of tryptophan synthase from E. coli (2400 units/mg protein [39]). A specific activity of 1200 units/mg protein has been determined independently by Bartholmes et al [48]. The value of 660 units/mg protein for our final preparation (Table 1) indicates that the enzyme is not maximally active, perhaps by side chain amide hydrolysis or some other, uncontrolled chemical modification of the protein.…”
Section: Discussionmentioning
confidence: 75%
“…As a result of such difficulties, more sophisticated purification procedures have been developed and a great majority of multienzyme complexes have been shown to be synthetized as multifunctional proteins. But even in such conditions, the yield of the multifunctional protein species is low, for example, with tryptophan synthetase (Bartholmes et al 1979), meaning that part of the activity is likely to be carried by smaller species. We should not, however, take it for granted that the observed proteolysis is always artifactual; it may well have some physiological importance.…”
Section: Discussionmentioning
confidence: 98%
“…These results were consistent with the idea that the tryptophan synthase of the more highly evolved sporeforming bacilli existed as an a@ species. Such a species might have represented an evolutionary intermediate toward the ap fusion product described in some of the lower eukaryotes (Tsai et al 1974;Dettwiler and Kirschner 1979;Bartholmes et al 1979). However, a more detailed examination of the factors affecting the association of the a and p subunits in B. subtilis determined the conditions necessary for the formation of higher molecular weight complexes.…”
Section: Discussionmentioning
confidence: 98%